A conservation landscape for the Dry Chaco based on species habitat suitability - Cuyckens, Griet An Erica (Ethnobiology and Conservation, 2021)
The Dry Chaco (DCH) is a biodiversity-rich region that contains the largest dry forest in the world. It is seriously endangered and has one of the fastest deforestation rates. Yet, very few conservation efforts have been undertaken to protect this ecosystem, and information to develop efficient and sustainable land-use plans is scarce. This study aimed to design a conservation landscape that would maximize the conservation of the DCH’s ecological integrity, endangered species, and ecological and evolutionary processes. Five focal species of high conservation value were chosen based on their ecological roles, conservation status, or endemism: white-lipped peccary Tayassu pecari, chacoan peccary Catagonus wagneri, giant anteater Myrmecophaga tridactyla, tapir Tapirus terrestris, and giant armadillo Priodontes maximus. We used interviews with local informants to obtain information on species presence and location. Their habitat suitability was modelled and ranked using Maxent software. A conservation landscape was designed by overlapping these spatially explicit models. A systematic conservation planning framework was followed, considering habitat connectivity using Zonation. Interviews proved to be useful for conservation planning in this region with longstanding close ethnozoological relationships. The spatial design obtained was compared with existing land-use policies and protected areas to discuss conservation strategies that could be efficient if applied in the DCH and considering land sharing vs. land sparing conservation strategies. There is a large surface of suitable habitat for the studied species, but their conservation cannot be ensured with the present conservation schemes. We consider land-sharing as a feasible conservation strategy for this region and its species, and identified areas that should be preserved and their optimal connections to increase conservation opportunities for the Dry Chaco.